Environmental Governance PT. Surya Saga Utama Post Mining in North Kabaena, Mapila Village, Bombana Regency in Towards Sustainable Development - AL Muhajir Haris (Journal La Sociale, 2021)
Environmental Governance is an integrated effort in the utilization, arrangement, maintenance, supervision, restoration and development of the environment. The goal in Environmental Governance is to achieve the sustainability of human relations with the environment as the goal of complete human development. This paper describes how environmental governance is in sustainable mining management in Kabaena Utara. This study uses a qualitative descriptive study, this research focuses on post-mining environmental management and as many as 15 informants between the government and the community. The results of this study generally describe the Control of Environmental Damage and Pollution regarding environmental management in Bombana Regency in terms of not being well-managed and not yet maximizing the protection of conservation areas from damage due to uncontrolled and exploitative use of natural resources.